2002
DOI: 10.1126/science.1073163
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Apoptosis by Anthrax Lethal Factor Through p38 MAP Kinase Inhibition

Abstract: The bacterium Bacillus anthracis causes the death of macrophages, which may allow it to avoid detection by the innate immune system. We found that B. anthracis lethal factor (LF) selectively induces apoptosis of activated macrophages by cleaving the amino-terminal extension of mitogen-activated protein kinase (MAPK) kinases (MKKs) that activate p38 MAPKs. Because macrophages that are deficient in transcription factor nuclear factor κB (NF-κB) are also sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
443
6
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(478 citation statements)
references
References 28 publications
25
443
6
4
Order By: Relevance
“…Two principal B. anthracis toxin components, lethal factor (LF, a Zn 2+ -protease) and edema factor (EF, a calmodulin-and Ca 2+ -dependent adenylate cyclase) are enzymes transported into cells by a third polypeptide, PA; combinations of PA with LF and EF yield B. anthracis lethal toxin (LT) and B. anthracis edema toxin (ET), respectively, that function as bacterial virulence factors in producing many of the symptoms of anthrax [13][14][15][16][17][18]. The pivotal role played by PA in toxin cell entry forms the basis for the current licensed anthrax vaccine, AVA (Biothrax TM ), a sterile culture filtrate of avirulent, non-encapsulated, B. anthracis (stimulated to produce relatively large amounts of PA) mixed with formalin and benzethonium chloride, and combined with aluminum hydroxide [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two principal B. anthracis toxin components, lethal factor (LF, a Zn 2+ -protease) and edema factor (EF, a calmodulin-and Ca 2+ -dependent adenylate cyclase) are enzymes transported into cells by a third polypeptide, PA; combinations of PA with LF and EF yield B. anthracis lethal toxin (LT) and B. anthracis edema toxin (ET), respectively, that function as bacterial virulence factors in producing many of the symptoms of anthrax [13][14][15][16][17][18]. The pivotal role played by PA in toxin cell entry forms the basis for the current licensed anthrax vaccine, AVA (Biothrax TM ), a sterile culture filtrate of avirulent, non-encapsulated, B. anthracis (stimulated to produce relatively large amounts of PA) mixed with formalin and benzethonium chloride, and combined with aluminum hydroxide [19].…”
Section: Discussionmentioning
confidence: 99%
“…Samples were retrieved from −70 • C storage that met preestablished criteria: (a) Vaccinations must have occurred within defined time intervals after receipt of the initial AVA injection (day 0 [dose #1], day 14 [range [11][12][13][14][15][16][17][18][19][20][21] ). (b) Pre-injection sera were defined as those taken on the day of each vaccine dose.…”
Section: Methodsmentioning
confidence: 99%
“…p38 is not only reported to be phosphorylated and activated to mediate cell apoptosis [7][8][9], but also to have cell protective effects under certain circumstances [10,11]. Why p38 has opposing functions in determining cell fate in different situations remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Survival of activated macrophages critically depends on both NF-kB and the p38 MAP kinase. 28 Work by Michael Karin and co-workers 29 showed that p38 controls the induction of a subset of NF-kBregulated genes by triggering MSK1/2-dependent phosphorylation of CREB, whose binding sites are highly represented in a subset of NF-kB/p38-coregulated genes. The dependence of survival genes on both NF-kB and p38 specifically links macrophage survival to the induction of both pathways and provides a simple paradigm of how parallel signaling events generate a transcriptional cross-talk.…”
Section: Nf-jb Extrinsic Mechanisms Gene-specific Control By Partner mentioning
confidence: 99%